Surface treatment of Mixed-Halide CsPb(BrxI1-x)3 perovskite quantum dots for thermal stability enhancement. (February 2022) - Huynh, Kim Anh; Nguyen, Tuan Van; Bae, Sa-Rang; Do, Ha Huu; Heo, Do Yeon; Le, Quyet Van; Jang, Ho Won; Ahn, Sang Hyun; Kim, Soo Young
Highlights: The thermal stability of mixed halide perovskite quantum dots CsPb(Brx I1-x )3 ( x = 0.2, 0.5, 0.8) was investigate. Surface passivation without destruction of optical properties. The phase segregation of mixed halide was successfully suppressed by surface passivation strategy. Abstract: In this study, the thermal stability of mixed-halide CsPb(Brx I1-x )3 perovskite quantum dots was investigated by monitoring its absorption, photoluminescence spectra, and X-ray diffraction. CsPb(Br0.8 I0.2 )3 was found to be the most stable composition at a constant temperature of 100 °C for up to 96 h, although some agglomeration was observed. In contrast, CsPb(Br0.2 I0.8 )3 revealed the most unstable composition under the same conditions as the aggregated iodide-rich domain easily transformed into the yellow-colored, non-luminescent δ-phase. CsPb(Br0.5 I0.5 )3 also showed phase segregation, where its original phase separated into bromide-rich and iodide-rich domains. By passivating the surface of mixed-halide perovskite, the particle agglomeration of CsPb(Br0.8 I0.2 )3 and phase segregation of CsPb(Br0.5 I0.5 )3 were significantly suppressed; however, the prevention of CsPb(Br0.2 I0.8 )3 phase transformation was less successful. Graphical abstract: Image, graphical abstract